PERILAKU PENGGUNAAN E-WALLET KARYAWAN BAGIAN PRODUKSI PT PRATAMA ABADI INDUSTRI (JX) SUKABUMI - Rizki Amalia; Mia Agustina Puspasari (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
This study aims to determine the behavior of using e-wallet in the financial transactions of employees of the Production Department at PT Pratama Abadi Industri (Jx). This study uses a qualitative-descriptive approach. There are 53 informants/respondents. Research data obtained through the collection of questionnaires and interviews. The results showed that (1) the use of e-wallet was very familiar among young employees of the Production Division of PT Pratama Abadi Industri (Jx); (2) Shopeepay and Dana as frequently used e-wallet platforms; (3) The use of e-wallet seems easy; (4) The use of e-wallet is also practical because it can be accessed from a smartphone.